Clinicopathological feature of a resected large mixed squamous cell and glandular papilloma: A case report. (April 2022) - Kawamoto, Nobutaka; Okita, Riki; Hayashi, Masataro; Osoreda, Hisayuki; Inokawa, Hidetoshi; Murakami, Tomoyuki
Abstract: Introduction and importance: Solitary endotracheal papilloma is a rare benign lung tumor. It is classified into the following three histological subtypes: squamous cell papilloma (SP), glandular papilloma (GP), and mixed squamous cell and glandular papilloma (MSGP). MSGP is the rarest among them. Herein, we describe a case of a large MSGP. Case presentation: A 59-year-old woman underwent computed tomography for the examination of cough, and an 8.2-cm-sized lung mass was noted in the left lingual segment. Bronchoscopy revealed that the left B 5 lumen was completely occluded by a tumor. Transbronchial lung biopsy suggested GP; thereafter, a left upper lobectomy was performed. Macroscopic findings showed that the dilated B 5 lumen was filled with cauliflower-like tumors. Histopathological findings showed that the majority of the tumors had pseudostratified columnar epithelium, while some had stratified squamous epithelium. The patient was diagnosed with MSGP. Although koilocytosis-like changes, such as perinuclear halo and nuclear deformation, were observed in some portions of the squamous epithelium, immunohistochemical staining was negative for human papillomavirus (HPV). Clinical discussion: HPV infection is reportedly associated with SP but not with GP and MSGP. Therefore, MSGP is considered to be caused by squamous metaplasia of a part of GP; this hypothesis is consistent with the present case. However, only one case of MSGP with HPV infection was recently reported, and the etiology and histological features of MSGP remain unclear. Conclusion: There are few reported cases of MSGP, and further case reports are needed to clarify its pathogenesis. Highlights: Human papillomavirus (HPV) infection is related to squamous cell papilloma. HPV infection is not related to mixed squamous cell and glandular papilloma (MSGP). MSGP is caused by squamous metaplasia of glandular papilloma. Accumulation of more case reports on MSGP is required to elucidate its pathogenesis.